Ethical and humanistic challenges in artificial intelligence and robotics: Metasynthesis - Bustamante-Cabrera, Gladys Inés (2024)
The quest of human beings to identify themselves as rational and creative beings has led to the development of Artificial Intelligence (AI) as a tool to emulate human thought and reinforce with automation various areas of knowledge. However, it is unavoidable to approach the ethical and humanistic challenges that are generated in the creation of AI. The aim of the study is to analyze the ethical implications of the use of AI and robots in society. To this end, a systematic review of 221 documents was carried out, selecting for analysis 12 publications on the legal conditions and responsibility of machines and their creators, as well as the ethical responsibility that lies in their use. The results show the need for clear regulatory frameworks to address the ethical and legal responsibility of autonomous systems and the protection of individual rights, suggesting debates on the emerging bioethical issues of the increasing integration of AI, robotics and the potential impact of transhumanism as a growing paradigm of human evolution.